Communication Strategies to Attract Public Interest in Trans Cirebon Services - Siti Aisah; Rico Yohanes Lumban Gaol; Farida Nurfalah (Journal of Social Science, 2025)
There is concern among the public about the lack of information regarding departure schedules, bus stop locations, and payment methods for the Trans Cirebon service. This qualitative study aims to determine the communication plans of the management in attracting public interest. Data was obtained through observation interviews and literature studies, then analyzed using the Miles and Huberman Model. The research findings indicate that the main issues are subsidies and insufficient information dissemination. The policy messages formulated emphasize safety, comfort, affordable fares, and customer testimonials. The implementation program involves the Transportation Department, PD Pembangunan, and PT BIG, with communication activities conducted through social media, public awareness campaigns, and direct outreach. Among the public, passenger feedback emphasized the importance of utilizing social media platforms like TikTok and Instagram to increase public interest in the Trans Cirebon service. The research recommendations suggest the need for more thorough communication planning by forming a communication team to analyze communication flow issues and challenges, as well as the selection of media and messages to achieve effective results